2001
DOI: 10.1021/jo001449d
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Calculations of the Effect of Fluorine Substitution on the Cyclobutylcarbinyl to 4-Pentenyl Radical Rearrangement

Abstract: The effects of fluorine substitution on the cyclobutylcarbinyl to 4-pentenyl radical rearrangement and on the strain of cyclobutane have being studied using density functional theory, the ring-opening being modestly inhibited and the strain generally not greatly affected. Perfluorocyclobutane is predicted to have 6 kcal/mol less strain than cyclobutane. Cyclizations of 1,1,2,2-tetrafluoro- and 1,1,2,2,3,3-hexafluoro-4-pentenyl radicals should be significantly enhanced ( approximately 2400 times faster) relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 27 publications
(47 reference statements)
0
14
2
Order By: Relevance
“…Rearrangement of 10 with a strong Lewis acid was (4) expected to yield ketone 11, a well precedented transformation of fluoroepoxides [8], but gave instead octafluorocyclopentene (12) with extrusion of carbon monoxide (Eq. (5)). Apparently the desired process was subverted by strain in the ring system, which caused a C-C bond shift to preclude fluorine migration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rearrangement of 10 with a strong Lewis acid was (4) expected to yield ketone 11, a well precedented transformation of fluoroepoxides [8], but gave instead octafluorocyclopentene (12) with extrusion of carbon monoxide (Eq. (5)). Apparently the desired process was subverted by strain in the ring system, which caused a C-C bond shift to preclude fluorine migration.…”
Section: Resultsmentioning
confidence: 99%
“…We initially assumed that this value represents an upper limit for the free energy of cleavage of the central bond of bicyclopentane 8, as is the case for the inversion barrier of the parent bicyclopentane (5). However, theoretical calculations point to a different conclusion.…”
Section: (20)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cyclobutanes can be formed by intramolecular addition of carbanions or radicals to C-C double bonds only if the latter are substituted with electron-withdrawing groups (see, e.g., Schemes 9.20 and 9.21) [81] or otherwise activated toward attack by nucleophiles. Activation by an alkynyl group or a cumulated double bond can be sufficient to promote cyclobutane formation (Scheme 9.20).…”
Section: Formation Of Cyclobutanesmentioning
confidence: 99%
“…[5][6][7] 1-Pentene is an important decomposition product of normal alkyl, and radical attack on it will produce 1-pentenyl radicals, especially in combustion processes. 8,9 1-Pentenyl is an important functional group, but there are only few literatures 10,11 regarding its reaction mechanism. Tsang 11 predicted some decomposition rate constants of 1-pentenyl radicals, but density functional theory (DFT) studies on its reaction mechanism were never reported.…”
Section: Introductionmentioning
confidence: 99%